2007
DOI: 10.1177/0269215506071251
|View full text |Cite
|
Sign up to set email alerts
|

Stress in caregivers of aphasic stroke patients: a randomized controlled trial

Abstract: Stroke caregiver support, education and training programmes have short-term effects on caregiver stress levels but are likely to require ongoing involvement to maintain their effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 21 publications
0
72
0
7
Order By: Relevance
“…Other research has highlighted the importance of routine and real-time telephone interventions in which healthcare providers supply information about stroke [18]. Similarly, stroke caregiver support, education, and training programs are effective in reducing stoke caregiver stress levels [19]. And largescale reviews and meta-analyses have generally suggested that caregiver education, counseling, and support interventions by telephone and in person are effective in reducing caregiver stress; improving family functioning, caregiver mental health, psychosocial functioning, and knowledge; and reducing the anxiety and depression of people with stroke [11,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Other research has highlighted the importance of routine and real-time telephone interventions in which healthcare providers supply information about stroke [18]. Similarly, stroke caregiver support, education, and training programs are effective in reducing stoke caregiver stress levels [19]. And largescale reviews and meta-analyses have generally suggested that caregiver education, counseling, and support interventions by telephone and in person are effective in reducing caregiver stress; improving family functioning, caregiver mental health, psychosocial functioning, and knowledge; and reducing the anxiety and depression of people with stroke [11,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should be responsive and tailored to both the needs of the care of the survivor and the unique needs of the family caregiver. 25,27,38,40,41,[44][45][46][47][48][49][50][51][52][53][54][55][56][58][59][60][61] 17 (53.1) 4 (23.5) 16 (94) Stroke survivor-caregiver dyad 26,[28][29][30][31][32][33][35][36][37]39,42,43,57,62,63 15 ( Psycho-educational 26,29,33,37,39,42,58 7 (21.9) 6 (85.7) 6 (85.7)Skill building and psycho-educational 25,27,28...…”
mentioning
confidence: 99%
“…This figure underlines the extent of the burden of care that partners carry [26] [27]. Particularly partners who face the loss of communication abilities in their family member due to aphasia may struggle [28].…”
Section: Rationale For the Implementation Of A Cpt Programmementioning
confidence: 97%